DIPLOMASI BUDAYA JEPANG DALAM MENINGKATKAN KUNJUNGAN WISATAWAN INDONESIA KE JEPANG MELALUI STRATEGI COOL JAPAN PERIODE 2012-2018 - Ilham Yogy Yuriansyah (2020)
Every year the country of Japan receives millions of foreign tourists whose numbers continue to experience a significant increase each year, especially in 2012-2018. This thesis will discuss Cool Japan Strategy which consists of various public diplomacy activities as one of the factors in increasing foreign tourist arrivals in Japan, especially Indonesia. Cool Japan Strategy as a tool to mobilize soft power assets owned by the Japanese state in order to achieve Japan's national interests related to tourism. This thesis will use the concept of cultural diplomacy and the concept of national interest, to analyze the Cool Japan Strategy implemented by Japan. So in this thesis will discuss various activities of national interest to mobilize Japanese cultural diplomacy under the Cool Japan Strategy to attract foreigners' interest in visiting Japan, especially from Indonesia